A Review of Surface Engineering of Graphene for Electrochemical Sensing Applications - Ijeomah, Geoffrey; Fahmi, Samsuri; Mohamad Adzhar, Md Zawawi (Penerbit Universiti Malaysia Pahang, 2017)
The outstanding properties of graphene arising from its monoatomic thickness, highly conjugated and twin-dimensionality merit attention for plethora of scientific and commercial applications. In this present review, the functionalization of surface chemistry of graphene is investigated to isolate its advantages over non-engineered materials for sensor research and related chemical and electrochemical sensing applications. The review also discuss new perspectives in the employment of these nano-engineered materials in chemical sensing and biosensing applications.